Building Energy Consumption in US, EU, and BRIC Countries. (2015) - Berardi, Umberto
Abstract: This paper presents and discusses data taken from several studies about the building energy consumption in US, EU, and BRIC (Brazil, Russia. India, China) countries. Most of the current researches about energy consumptions deals with statistics in a specific country. However, international comparisons are useful to discover historical, actual, and energy consumption trends. Data presented in reports of the World Bank, the United Nations Environment Program, the Intergovernmental Panel on Climate Change, and the International Energy Agency are compared with national reports as well as with research studies. This analysis shows that the BRIC countries have already overcome the total energy consumption of developed countries, and the expansion of their building stock raises an imperative urgency for energy efficiency in buildings. At the same time, this paper shows that the measures actually adopted in developed countries are insufficient to guarantee a significant reduction in their energy consumption inbuildings.